The Development of an Authentic Assessment Instrument Based on Google Sites to Measure the Learning Outcomes of the IPAS Project - Setiawan, Joko Tia; Sudarmin, Sudarmin; Isnaeni, Wiwi (International Journal of Active Learning, 2024)
This research aims to explain the form of an authentic assessment instrument based on Google Sites to measure the learning outcomes of the IPAS Project on the Earth and Space aspects, as well as test its validity, reliability and practicality. The test subjects were 110 students. The data analysis technique uses Aiken's V for content validity, CFA for construct validity, ICC for interrater reliability, CR and VE for construct reliability, Cronbach's Alpha for internal reliability of the instrument, and percentage for practicality. The research results obtained three forms of authentic assessment instruments based on Google Sites that measure the learning outcomes of the IPAS Project, namely independent assignment assessment sheets, group project assignment assessment sheets, and objective tests. The instrument is valid in terms of both content validity and construct validity, except for items B2 and B4 so they must be removed from the model. The instrument is reliable in terms of interrater reliability, instrument reliability and construct reliability, except for dimension C which has a VE value below the criteria. A very practical instrument to use in measuring the learning outcomes of the IPAS Project.